2021
DOI: 10.1097/mou.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

Surgical procedures for male infertility: an update

Abstract: Purpose of review The aim of this review is to provide an overview of surgical treatment options for male infertility including varicocelectomy, treatment of ejaculatory duct obstruction, vasovasostomy, and sperm extraction, and to review recent advances in techniques and technologies that may improve operative outcomes. Recent findings Microscopic subinguinal varicocelectomy has been shown to have the highest success rates with lowest rates of complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Male infertility is a major issue in human reproductive health, affecting more than 20 million men worldwide and preventing natural conception (Niederberger, 2020;Visser et al, 2020). Asthenozoospermia, a symptom frequently observed in infertile men with less progressive motile sperm (Cooper et al, 2010), is caused by morphological and functional defects of the sperm flagellum.…”
Section: Introductionmentioning
confidence: 99%
“…Male infertility is a major issue in human reproductive health, affecting more than 20 million men worldwide and preventing natural conception (Niederberger, 2020;Visser et al, 2020). Asthenozoospermia, a symptom frequently observed in infertile men with less progressive motile sperm (Cooper et al, 2010), is caused by morphological and functional defects of the sperm flagellum.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have reported improved semen parameters in 50-65% of infertility cases and a pregnancy rate of 20-30% following TURED [1]. Although TURED is endorsed as a treatment for EDO and performed by urologists for male fertility and oncologic cases [2,3], its effectiveness is not well understood, and further research is necessary to ascertain the specific patient subgroups that will derive the most benefit from this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the treatment of VCs can be divided into two categories: surgical treatment and interventional treatment. Although each approach has advantages and complications, the incidence of hydroceles and recurrence rate after MSV are the lowest [3] . Based on MSV, some improvements were made using the natural folds of the scrotal skin, and some unexpected benefits were obtained.…”
mentioning
confidence: 99%